2019
DOI: 10.1007/s10853-019-03785-1
|View full text |Cite
|
Sign up to set email alerts
|

A high-strength heterogeneous structural dual-phase steel

Abstract: The strengthening and ductilization of steels are of great importance to weight reduction of vehicles. In this work, the strength-ductility synergy of dual-phase (DP) steels was obtained by properly tailoring the structural heterogeneity, including the distribution and fraction of constituent phases. It was demonstrated that heterogeneous structural DP steels with high volume fraction of martensite (from 64 to 83%) led to a good combination of strength and ductility. Compared with the cold-rolled sheets, the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…After holding at 740, 760, 780, and 800 • C for a long time, 36%, 48%, 65%, and 85% reverse austenite was obtained, respectively. Heterogeneous microstructure with hard and soft phases is characterized by microstructural heterogeneity and/or compositional heterogeneity, which lead to a dramatic difference in strength between different structures [4,[6][7][8]. The strength mismatch between different structures will cause the inhomogeneous deformation in local areas, by which a strain gradient around the interfaces could be triggered, and geometrically necessary dislocations (GNDs) could build up.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After holding at 740, 760, 780, and 800 • C for a long time, 36%, 48%, 65%, and 85% reverse austenite was obtained, respectively. Heterogeneous microstructure with hard and soft phases is characterized by microstructural heterogeneity and/or compositional heterogeneity, which lead to a dramatic difference in strength between different structures [4,[6][7][8]. The strength mismatch between different structures will cause the inhomogeneous deformation in local areas, by which a strain gradient around the interfaces could be triggered, and geometrically necessary dislocations (GNDs) could build up.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, the steels with higher martensite fraction (IA780 and IA800) showed higher back stress. The effective stress is closely related to the forest hardening in intercritical ferrite [7]. The plastic strain will be more concentrated in the intercritical ferrite during the tensile test, and more dislocations are thus generated in this microconstituent.…”
Section: Analysis Of Mechanical Behavior 421 Strength and Work Harden...mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrary to the observed deformation behaviour as homogeneous in a macroscopic viewpoint, multiphase material actually experiences deformation inhomogeneity through strain partitioning among the constituent phases. 3436 Stanford et al 37 also show the strain partitioning behaviour in multiphase steel under cyclic loading, where it was observed that the plastic strain accumulation is predominant in ferrite instead of bainite. Besides strain partitioning between constituent phases, a variation in crystallographic misorientation, GND and slip occur while having an exposure at different degrees of cyclic plastic strain in individual grain.…”
Section: Introductionmentioning
confidence: 98%
“…Creating a heterogeneous microstructure in HSLA steels has proven to be a new method of addressing the above problem [8][9][10][11]. Heterogeneous microstructure has a significant difference in strength among different domains, generally containing a hard martensite phase embedded in the soft austenite and/or ferrite matrix [12][13], which can be fabricated by intercritical annealing [14][15]. Compared with conventional Q&T processing, intercritical annealing can markedly increase the ductility and toughness and lower the YR of low carbon low alloy steels.…”
Section: Introductionmentioning
confidence: 99%